# Solving Maths Equation!

Can some one help me solve the fowllowing equations:

1,Factorize:

a, x2-(y-z)2

2,Make a the subject of the fomula p=ab+2bc+3ac

3,Make m the subject of the fomula mx=2(m+c)

4,In fomula y=(1/2)(x+3) If the value of y is increased by 1, find the corresponding increase in the value of x.

5, Make x the subject of the fomula b=2x +(1-x)a

You can send the answer to my e-mail; laura40692@yahoo.com.hk

Thanks.

Rating

I think it is better to tell you in this way...

1,Factorize:

a, x2-(y-z)2

Formula: x^2-y^2 = (x+y)(x-y)

So, x2-(y-z)2

= (x-y+z)(x+y-z)

Factorize it by grouping:

=a(b-d) -c(b-d)

=(a-c)(b-d)

2,Make a the subject of the fomula p=ab+2bc+3ac

Group the things contain a into group:

p-2bc=a(b+3c)

a= (p-2bc)/b+3c

3,Make m the subject of the fomula mx=2(m+c)

The same way:

mx=2m+c

m(x-2)=c

m=c/(x-2)

4,In fomula y=(1/2)(x+3) If the value of y is increased by 1, find the corresponding increase in the value of x.

Expand:

y=x/2 + 1.5

Let see:

If y = 1 ,

1=x/2+1..5

-0.5=x/2

x=-1

If y=2,

2=x/2+1.5

0.5=x/2

x=1

If y=3,

3=x/2+1.5

1.5=x/2

x=3

So we can see ,If the value of y is increased by 1,the corresponding increase in the value of x is 2.

5, Make x the subject of the fomula b=2x +(1-x)a

b=2x+a-ax

b-a=x(2-a)

x=(b-a)/(2-a)

2009-01-04 13:39:14 補充：

001 is wrong.

a(b-d)-c(b-d)<>ac(b-d)

when we factorize,

we take out the common factor

for example,

in this question,

the factor is (b-d)

after we take out (b-d) from both terms,

we remain: a and -c

so the ans is (a-c)(b-d)

2009-01-04 13:42:20 補充：

Oh I want to ask a question:

a, x2-(y-z)2

it is x square or x times 2?

if it is x times 2,

2x - 2(y-z)

=2(x-y+z)

001 is wrong again!

In -2(y-z)

we have 負負得正right?

so it is not -2z, is 2z

Source(s): Me
• 1a)x2-(y-z)2

=2x-2y+2z

=2(x-y+z)

=a(b-d)-c(b-d)

=(a-c)(b-d)

2)p=ab+2bc+3ac

p=ab+3ac+2bc

p=a(b+3a)+2bc

p-2bc=a(b+3a)

a=(p-2bc)/(b+3a)

3)mx=2(m+c)

mx=2m+2c

mx-2m=2c

m(x-2)=2c

m=(2c)/(x-2)

4)If y = 1 ,

1=x/2+1..5

-0.5=x/2

x=-1

If y=2,

2=x/2+1.5

0.5=x/2

x=1

Therefore,if the value of y is increased by 1,the corresponding increase in the value of x is 2.

5)b=2x +(1-x)a

b=2x+a-ax

b=2x-ax+a

b=x(2-a)+a

b-a=x(2-a)

x=(b-a)/(2-a)

Source(s): myself
• 1)2x-2(y-z)

=2x-2y-2z

=2(x-y-z)